Social capital and entrepreneurial financing choice - Dudley, Evan (Journal of Corporate Finance, 2021)
This paper investigates the influence of social capital on young firms' financing arrangements. Using a sample of U.S. start-ups, I find that social capital, as captured by secular norms and social networks in the entrepreneur's county, increases access to outside financing and reduces reliance on owner equity to finance the new venture. Financing to entrepreneurs located in counties with greater social capital involves higher amounts of leverage in the form of outside debt. This finding persists in a difference-in-difference test that controls for unobservable geographic determinants of capital structure.